The P2X(7) receptor in retinal ganglion cells: A neuronal model of pressure-induced damage and protection by a shifting purinergic balance - Mitchell, Claire H. (Springer Netherlands, 2008)
Retinal ganglion cells process the visual signal and transmit it along their axons in the optic nerve to the brain. Molecular, immunohistochemical, and functional analyses indicate that the majority of retinal ganglion cells express the ionotropic P2X(7) receptor. Stimulation of the receptor can lead to a rise in intracellular calcium and cell death, although death does not involve the opening of a large diameter pore. Adenosine acting at A(3) receptors can attenuate the rise in calcium and death accompanying P2X(7) receptor activation, suggesting that dephosphorylation of ATP into adenosine is neuroprotective and that the balance of extracellular purines can influence neuronal survival. Increased intraocular pressure can lead to release of excessive extracellular ATP in the retina and damage ganglion cells by acting on P2X(7) receptors, implicating a role for the receptor in the loss of ganglion cell activity in glaucoma. In summary, the activation of P2X(7) receptors has both physiologic and pathophysiologic implications for ganglion cell function. These characteristics may also provide an insight into the contributions the P2X(7) receptor makes to neurons elsewhere.